2010
DOI: 10.1038/ijo.2010.236
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and type 2 diabetes in Northern Canada's remote First Nations communities: the dietary dilemma

Abstract: First Nations populations in Northwestern Ontario have undergone profound dietary and lifestyle transformations in less than 50 years, which have contributed to the alarming rise in obesity and obesity-related diseases, in particular type 2 diabetes mellitus. Even though the genetic background of First Nations peoples differs from that of the Caucasians, genetics alone cannot explain such a high prevalence in obesity and type 2 diabetes. Modifications in lifestyle and diet are major contributors for the high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 74 publications
(86 reference statements)
0
39
0
Order By: Relevance
“…that region of the country that is north of the 50th parallel) are facing a food crisis brought about by the introduction of processed foods and a decrease in the consumption of healthy land-based foods due to environmental decline, restrictive policies, and cultural change (Thompson et al 2011). Processed foods and poor access to perishables contribute to the increased occurrence of Type II diabetes and heart disease in these communities (Martens et al 2007, Haman et al 2010. Impacts are aggravated by high rates of unemployment and poverty (Ho et al 2008, Haman et al 2010, and devastation caused by the residential school system and the "Sixties Scoop" designed to undermine and assimilate Indigenous livelihoods and traditional cultures (G. McKay, personal communication, 17 October 2009;Partridge 2010).…”
Section: Introductionmentioning
confidence: 95%
“…that region of the country that is north of the 50th parallel) are facing a food crisis brought about by the introduction of processed foods and a decrease in the consumption of healthy land-based foods due to environmental decline, restrictive policies, and cultural change (Thompson et al 2011). Processed foods and poor access to perishables contribute to the increased occurrence of Type II diabetes and heart disease in these communities (Martens et al 2007, Haman et al 2010. Impacts are aggravated by high rates of unemployment and poverty (Ho et al 2008, Haman et al 2010, and devastation caused by the residential school system and the "Sixties Scoop" designed to undermine and assimilate Indigenous livelihoods and traditional cultures (G. McKay, personal communication, 17 October 2009;Partridge 2010).…”
Section: Introductionmentioning
confidence: 95%
“…The influx of store-bought foods has changed subsistence lifestyles: community stores provide an ease to food acquisition, with detriments of economic dependence and negative health impacts associated with processed foods (Haman 2010). New food sources have not replaced traditional foods, as half of Tłichǫ citizens' diets still consist of traditional foods (Tłichǫ 2012: 23).…”
Section: Commensality: Sharing Foodmentioning
confidence: 99%
“…The decline of caribou herd populations in northern Canada at the turn of the century, and subsequent hunting restrictions of the Bathurst herd (see Adamczewski et al 2009), has changed the relationship between the Dene and the caribou, and the Dene now rely more heavily on imported foods (Haman 2010). Yet ontological assumptions about the nature of caribou have not changed, and they inform Dene responses to the current crises in relationship.…”
Section: Dene Foodways In the Era Of Climate Changementioning
confidence: 99%
“…Traditional or wild food consumption has many nutritional (Dewaillly et al 2001;Kusunoki et al 2003;Johnson-Down and Egeland, 2010;Haman et al 2010) and cultural (Kelm, 2001;Damman et al 2008) benefits. Studies have shown that circumpolar populations shifting away from the consumption of wild foods harvested from the land have a tendency to replace them with lower quality foods high in starches, fat, and sugar.…”
Section: Introductionmentioning
confidence: 96%